(untitled) (De Legibus - Law Journal, 2022)
Remarks delivered at the homage of the Faculty of Law of Lusófona University to Mr. Councilor António Quirino Soares and to Mr. Councilor Francisco Ferreira de Almeida, on September 14, 2021.